Avaliação da qualidade fisiológica de sementes de milho e soja por espectroscopia no infravermelho próximo - Alvarez, Richard Alcides Molina (2018)
The physiological quality of seeds is fundamental in the implantation of a crop, making it imperative to use methodologies that help to determine the deterioration or the vigor itself, being fundamental the efficiency and effectiveness of the applied tests. The objective of this study was to verify the potential of the Near Infrared Reflectance Spectroscopy (NIRS) technique using Bruker brand equipment to separate different levels of physiological quality of corn and soybean seeds, to correlate the results with the conventional vigor tests recommended for each crop . Samples with different levels of vigor were obtained for each species using the accelerated aging method to deteriorate them. In order to evaluate the profile of the samples, water content, germination, first germination count, field emergence and emergency velocity index were used for the two cultures, and in the electrical conductivity and tetrazolium tests for soybean; accelerated aging and cold test for corn. The NIRS analysis was performed using whole seeds with uniform humidity degree after deterioration, the data obtained by the equipment were analyzed by the PLS-DA method with the help of the software PIROUETTE. By conventional tests of vigor it was possible to distinguish several levels of vigor in both corn and soybean seeds. In the NIRS method, it was not possible to distinguish satisfactorily the quality levels, when the lots of each crop were studied individually, but when the most vigorous and less vigorous ones were grouped, an improvement in the response of classification of lots of corn seeds and with less intensity to the soybean, it was not enough to discriminate clearly the levels of physiological quality when related to the conventional tests of vigor.